Analisa Kelayakan Investasi Penambahan Modular pada Pertashop 3P.16102 Di Tanah Sareal Kota Bogor - Aka Arinda; Firdaus Sustanto; Wisdanto Mas Soeroto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Pertashop (Pertamina Shop) is a certain-scale outlet of Pertamina prepared to serve the needs of consumers for fuel, non-subsidized LPG, and other Pertamina retail products, with a focus on serving in areas that require Pertamina retail product services. Pertashop 3P.16102 is one of the Pertashops owned and managed by PT. Sri Rejeki Makmur Sentosa under the Dealer Owned Dealer Operated (DoDo) scheme. This Pertashop is located at Jl. Raya Kencana No.31, Tanah Sareal District, Bogor City, West Java. This Pertashop has been operating since January 2021 with current average fuel sales reaching 1,400 liters per day. One of the issues faced by this Pertashop is frequent operational closures due to running out of fuel stock. This occurrence is influenced by the limited storage tanks and the mismatch between delivery schedules and fuel receipt from Pertamina. The solution proposed by the company is to add 1 (one) modular unit with an upperground tank capacity of 3,000 liters. The purpose of this study is to determine and assess the feasibility of investing in the addition of a modular unit at Pertashop 3P.16102 quantitatively and qualitatively from an economic and technical aspect. The parameters used to review the investment are market potential calculation, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). These parameters will be considerations for management to assess the feasibility of this investment. From the analysis conducted, it was found that the market potential calculation was 5,676 liters per day, NPV was Rp 234,652,260.00, IRR was 43%, PP was 2 years, and PI was 1.7. Considering the market potential, NPV, IRR, PP, and PI, this project is economically feasible.